2021
DOI: 10.3897/asp.79.e67022
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the midgut epithelium in four diplopod species: histology, histochemistry and ultrastructure

Abstract: The middle region of the digestive system of millipedes, the midgut, is responsible for all processes connected with digestion, but also takes part in homeostasis maintenance thanks to the ability to activate many mechanisms which neutralize changes occurring at different levels of the animal’s body. Numerous millipede species are treated as bioindicators of the natural environment and they are exposed to different stressors which originate from external environment. To obtain all data on the functioning of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Columnar cells for enzyme absorption and secretion by apical surface with long regular microvilli, goblet cells for ionic homeostasis, endocrine cells for endocrine function, and regenerative cells for epithelium renewal by repairing and replenishing the worn‐out midgut epithelium that is lost during the digestive process [33,34] . They can be seen alone or in clusters close to the base of the midgut [35,36] . Numerous studies have shown that physiological alterations, such as variations in food absorption and digestion in the alimentary canal, can affect an insect‘s growth and development (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Columnar cells for enzyme absorption and secretion by apical surface with long regular microvilli, goblet cells for ionic homeostasis, endocrine cells for endocrine function, and regenerative cells for epithelium renewal by repairing and replenishing the worn‐out midgut epithelium that is lost during the digestive process [33,34] . They can be seen alone or in clusters close to the base of the midgut [35,36] . Numerous studies have shown that physiological alterations, such as variations in food absorption and digestion in the alimentary canal, can affect an insect‘s growth and development (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…[33,34] They can be seen alone or in clusters close to the base of the midgut. [35,36] Numerous studies have shown that physiological alterations, such as variations in food absorption and digestion in the alimentary canal, can affect an insect's growth and development (Figure 9). [37,38] As regarding, the treated larvae with 11 displayed severe deformation, obvious necrosis, columnar cell shortening, and significant apical region degeneration because apocrine secretion largely damaged the apices of epithelial cells, as illustrated in Figure 10.…”
Section: Histological Parametermentioning
confidence: 99%
“…Mitochondria are also responsible for the activation of numerous proteins or enzymes involved in the processes of survival or death (Bratic & Larsson, 2013; Faron et al, 2015; Hödl et al, 2010; Kühlbrandt, 2015; Rost‐Roszkowska, Poprawa, et al, 2021; Włodarczyk et al, 2017). All changes in their structure, membrane potential, or metabolism are related to degenerative processes (Bednarska & Świątek, 2016; Faron et al, 2015; Hödl et al, 2010; Nunnari & Suomalainen, 2012; Rost‐Roszkowska, Vilimová, et al, 2021; Włodarczyk et al, 2017; Xia et al, 2019). We observed changes in digestive cells' ultrastructure and the cell death processes according to prolonged gluten consumption.…”
Section: Discussionmentioning
confidence: 99%